Pengaruh Karakteristik Komite Audit terhadap Kualitas Audit - Yolanda, Chintia Faras; Dwita, Sany (Jurnal Eksplorasi Akuntansi, 2025)
This study examines the effect of audit committee characteristics, namely audit committee industry expertise, audit committee legal expertise, and audit committee gender diversity on audit quality. The population used in this study are non-financial sector companies listed on the Indonesia Stock Exchange in 2021-2023. The sampling technique in this study was purposive sampling, where the sample taken was 240 companies. The statistical method used in this research is multiple linear regression analysis. The results of this study are audit committee industry expertise, audit committee legal expertise, and audit committee gender diversity have no effect on audit quality. These findings suggest the theory linking audit committee characteristics with audit quality needs to be expanded or updated to consider other factors that may affect audit quality.